Kualifikasi Sumber Daya Insani Berbasis Kompetensi dan Integritas dalam Akad Murabahah di BMT Prima Lubuk Seberuk Kecamatan Lempuing Kabupaten Ogan Komering Ilir Sumatera Selatan - Muhammad Isnan (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2019)
This research means to know qualification of human resources in BMT Prima Lubuk Seberuk in an effort increases the performance of the employees. This research used survey method by using qualitative data. The data collection technique which is used is direct interview with related one or informant. This research concluded that the development effort of the human resources quality of BMT Prima Lubuk Seberuk is dominated by the employee who is not syariah based. This thing provided BMT Prima lubuk seberuk to encrease the competence and the integrity of the employees by giving sustainable coaching to all of the employees for developing the competence and the integrity which is syariah based. The effort of developing the competence and the integrity in BMT Prima lubuk seberuk is using management assembling of human resources strategy among the are planning, recruitment process, giving motivation, education process and coaching. The result of the research showed that so far the development effort of human resources which is based on competence and integrity at BMT Prima Lubuk Seberuk went well. Observation result of researcher who found that the assets develompemnt is more and more and the trust phase of the customer at BMT Prima lubuk seberuk is more and more. This thing indicated that in order to fulfill the qualification standard of the employee which is competence and integrity based at BMT Prima Lubuk Seberuk for now is reputed to fulfill the service to the costemer in finances institute whic is syariah based like at BMT Prima.